Conservação pós-colheita de frutos de tomateiro longa vida estrutural e com mutante rin, produzidos nas condições edafoclimáticas do sul do estado do Tocantins - Pereira, Miréia Aparecida Bezerra; Tavares, Aline Torquato; Silva, Edgard Henrique Costa [UNESP]; Alves, Anatércia Ferreira; Azevedo, Sebastião Márcio; Nascimento, Ildon Rodrigues (FapUNIFESP (SciELO), 2015)
The high temperature of growth environment can affect the postharvest quality of tomato fruits. In this situation, an alternative for the farmers is the use of hybrid cultivars that produce long shelf life fruit with longer postharvest shelf life when compared to normal varieties of fruits. The objective of this research was to compare the postharvest conservation of fruits of structural long shelf life tomato hybrids and with the mutant rin. The fruits evaluated were from fifteen tomato genotypes produced under the edaphoclimatic conditions of the southern State of Tocantins, being four of them long shelf life type hybrids (with rin allele) which were: Tyler, Rebeca, Carmem and AF 13527; nine of them structural long shelf life hybrids: Lumi, Débora Max, Michelli, Tammy, AF 12525, AF 11097, AF 13363, AF 13364 and AF 13525; and two normal fruit cultivars: Santa Clara and Drica. The fruits were harvested at the breaker stage and stored in a controlled environment (20 °C and relative humidity of 60%). The half-life firmness of fruits of genotypes with a structural genotypic long shelf life background ranged from 6.25 to 13.44 days for the genotypes Tammy and AF13525, respectively, not differing from the long shelf life genotypes with rin allele. Despite the fact that daytime temperatures are higher than those recommended for the tomatoes crops, it was observed that if the fruits are stored in appropriate conditions (20 °C and relative humidity of 60%), the color and firmness of the fruits with a long shelf life genotypes with rin allele and structural genotypic background evolve more slowly than the fruits of normal genotypes. Under these conditions, it took the fruits 7 to 8 days to acquire a red color on more than 80% of the surface after being harvested.
Postharvest conservation of structural long shelf life tomato fruits and with the mutant rin produced, in edaphoclimatic conditions of the Southern State of Tocantins
Keywords: Color; Firmness; Hybrids; Solanum lycopersicon